Experimental study of RC beams strengthened for bending by reinforced grout layer and connectors - CANAVAL,J. H. (2018)
Abstract This work is based on an experimental investigation of reinforced concrete beams strengthened to flexure for wrapping applying a type of metallic connector in the bond substrate/groute. The experimental program consisted of 5 beams used for reference (without strengthening), 5 beams reinforced with surface brushed texture substrate and 5 beams with metal connectors bonded to the substrate. The beams were submitted to four-point load bending test. Initially with a partial loading, executed the strengthening and were finally tested until the break. The strengthening was made up by the increase by graute, on the sides and bottom of the beam and reinforcing. The applied force, the displacement, deformations in steel and in concrete were measured. The reference beams failure by flexing with the calculated charges. The bending strengthening proved efficient, increasing the bearing capacity in 44% and the failure was by shear in the stretch without strengthening. Beams with connectors the increase was higher.